Perceived Effort in Football Athletes: The Role of Achievement Goal Theory and Self-Determination Theory - Monteiro, Diogo; Teixeira, Diogo S.; Travassos, Bruno; Duarte-Mendes, Pedro; Moutão, João; Machado, Sérgio; Cid, Luís (Frontiers in Psychology, 2018)
The main goals of this study were, to test the motivational determinants of athletes perceived effort in football considering the four-stage motivational sequence at the contextual level proposed by Hierarchical Model of Intrinsic and Extrinsic Motivation: task-involving, basic psychological needs, self-determined motivation and perceived effort. The multi-group analysis across different age-groups (U15, U17, U19, U21 years) and mediation role of basic psychological needs and self-determined motivation on the task-involving climate and the perceived effort were also analysed. Two independent samples of male football athletes (N= 403, N= 403), aged 13-20 were enrolled in this study. The results demonstrated that structural model provided a good fit to data for all samples under analysis, and was invariant across U17, U19, and U21. However, it was not invariant across U15 and U17, U19 and U21. Additionally, in the results from the mediation analysis, there were significant indirect effects in all samples, supporting theoretical by self-determination theory assumptions, reinforcing the importance of basic psychological needs satisfaction and behavioral regulation in the relation in analysis. The results allow concluding that when coaches promote a task-involving climate, the basic psychological needs satisfaction of athletes improves. This climate will facilitate the regulation of their behaviors towards more autonomous forms of motivation, with positive results in the perceived effort of the athletes.